2014
DOI: 10.1002/app.40844
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behavior induced by vitamin E and electron beam irradiation in ultra high molecular weight polyethylene

Abstract: Radiation cross‐linked ultra high molecular weight polyethylenes (UHMWPEs) have been successfully used as wear resistant bearing surfaces in total joint arthroplasty. A recent development in this field is the incorporation of the antioxidant vitamin E into radiation cross‐linked UHMWPE. This study investigates the effects of radiation cross‐linking and vitamin E incorporation on the dielectric behavior of UHMWPE. The dielectric relaxations of virgin and 0.1 wt % vitamin E‐blended UHMWPE and their irradiated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…7,8 It also accelerates the generation of particulate wear in joint components. [21][22][23][24][25][26][27][28] Vitamin E can either be blended into the UHMWPE resin prior to molding 29 or diffused into the implant after radiation. This initial increase in crosslinking indicated that it increases resistance of UHMWPE to wear and leads to the development of highly crosslinked UHMWPEs (HXLPEs), which were subjected to higher radiation doses of gamma or electron beam radiation (50-100 kGy dose range), not as a final sterilization step of the packaged implant but as a processing step for molded sheets and rods of UHMWPE, prior to the fabrication of the implant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 It also accelerates the generation of particulate wear in joint components. [21][22][23][24][25][26][27][28] Vitamin E can either be blended into the UHMWPE resin prior to molding 29 or diffused into the implant after radiation. This initial increase in crosslinking indicated that it increases resistance of UHMWPE to wear and leads to the development of highly crosslinked UHMWPEs (HXLPEs), which were subjected to higher radiation doses of gamma or electron beam radiation (50-100 kGy dose range), not as a final sterilization step of the packaged implant but as a processing step for molded sheets and rods of UHMWPE, prior to the fabrication of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] While irradiation has been unavoidable due to its large increase in wear resistance, post-radiation treatments to reduce free radical content in irradiated HXLPEs can be avoided by incorporation of a stabilizer, such as Vitamin E or other biocompatible antioxidants. [21][22][23][24][25][26][27][28] Vitamin E can either be blended into the UHMWPE resin prior to molding 29 or diffused into the implant after radiation. 30 The advantage of the latter over the former process is that it was shown that Vitamin E can decrease the formation of crosslinks in the amorphous regions by scavenging free radicals before crosslinking can occur.…”
Section: Introductionmentioning
confidence: 99%